Artificial Intelligence-Powered Integrity: Unveiling Students’ Techniques for Plagiarism Management in Thesis Proposal Writing - Zulkifli, Zulkifli (ETERNAL (English, Teaching, Learning, and Research Journal), 2024)
The research was conducted to investigate students’ strategies in managing plagiarism concerns in thesis proposal writing with the assistance of artificial intelligence such as chatgpt. This research employed a qualitative method with a case study design. Eight students from English Education Study Program of State University of Makassar were chosen as the subject of this research. Data were gathered through semi-structured interviews and document analysis. The findings reveal that students utilize paraphrasing strategies to manage the plagiarism concern regarding to writing thesis proposal with the assistance of artificial intelligent. Three types of strategies were identified: Quillbot paraphrasing, self-paraphrasing, and a combination of Quillbot and self-paraphrasing. These strategies proved highly effective in ensuring the academic integrity of students’ work and producing high-quality proposals.